An Atropisomerism Study of Large Cycloarylenes: [n]Cyclo‐4, 10‐Pyrenylenes' Case. Issue 24 (17th March 2023) - Kurosaki, Ryo; Morimoto, Hirofumi; Matsuo, Kyohei; Hayashi, Hironobu; Yamada, Hiroko; Aratani, Naoki
Abstract: An atropisomerism of large cycloarylenes was studied using [ n ]cyclo‐4, 10‐pyrenylenes ( n =6–21) as an illustrative example with two simple assumptions: (1) alternating configurations ( R, S, R, S, …) are thermodynamically most stable, and (2) three consecutive identical configurations ( R, R, R or S, S, S ) are prevented. Ni‐mediated coupling of a 5, 9‐diiodopyrene gave a series of directly‐linked cyclic pyrene oligomers in one‐pot reaction. As‐synthesized cyclic hexamer was assigned as an ( R, S, S, R, R, S ) structure, converted into an ( R, S, R, S, R, S )‐form upon heating. Cyclic heptamer consists of two types of C 2 symmetric structures predicted from assumption (2), one of which was convergent to one another by heating. Three atropisomers of cyclic octamer were analyzed from the possible five candidates by means of 1 H nuclear magnetic resonance (NMR) spectroscopy, and the conversion process to ( R, S, R, S, R, S, R, S ) configurations upon heating was investigated. In total, according to two simple rules, the analysis of atropisomerism could be performed smoothly. Abstract : Cyclo‐4, 10‐pyrenylenes of various ring sizes were obtained by coupling reactions at the 5, 9‐diiodo‐pyrene. Since systematic studies of macrocyclic atropisomerization dependent on their ring‐size remain challenging, these large cycloarylenes from 6mer to 8mer were investigated as illustrative examples according to simple assumptions.